Epidemiological, clinical and diagnostic aspects of feline otitis: a retrospective study of 103 cases from the dermatology service of a veterinary teaching hospital (2020‐2022) - L. Humeau; N. Do Dinh; H. Dropsy; N. Cochet‐Faivre (Journal of Small Animal Practice, 2026)
Objectives To describe the epidemiological characteristics, clinical features, diagnostic findings and underlying causes of feline otitis in cases presented to a French veterinary teaching hospital. Materials and Methods Medical records of cats diagnosed with otitis by the dermatology department of a veterinary teaching hospital between September 2020 and March 2022 were retrospectively reviewed. Signalment, clinical history, video‐otoscopic findings, cytology, imaging and histopathology results were collected. Results A total of 103 cats were diagnosed with otitis. Maine Coon, Sphynx, Turkish Angora and Selkirk Rex cats were significantly overrepresented. Age distribution showed increased case numbers in cats younger than 6 years, with another peak at 12 to 14 years of age. Chronic otitis represented 71.8% of cases. A primary cause was identified in 66.0% of cases, most frequently feline atopic syndrome, inflammatory polyps, neoplasia, isolated otitis media and otoacariasis. Staphylococcus spp. predominated in cultures (84.6%). Suppurative otitis was identified in 42 cats (40.8%). Video‐otoscopy demonstrated high sensitivity and specificity for inflammatory polyps and otoacariasis. Clinical Significance Feline otitis was predominantly chronic, with inflammatory polyps most commonly identified in younger cats and neoplasia in older cats; suppurative otitis was frequent and mainly associated with inflammatory polyps, otitis media and neoplasia. These findings emphasise the need for a comprehensive diagnostic approach to feline otitis, incorporating video‐otoscopy and advanced imaging to identify age‐related primary causes and guide clinical decision‐making.